2015
DOI: 10.1002/14651858.cd007394.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan detection for invasive aspergillosis in immunocompromised patients

Abstract: If we used the test at a cut-off value of 0.5 ODI in a population of 100 patients with a disease prevalence of 9% (overall median prevalence), two patients who have invasive aspergillosis would be missed (sensitivity 82%, 18% false negatives), and 17 patients would be treated unnecessarily or referred unnecessarily for further testing (specificity 81%, 19% false negatives). If we used the test at a cut-off value of 1.5 in the same population, that would mean that four invasive aspergillosis patients would be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 97 publications
2
121
0
6
Order By: Relevance
“…Albeit this an invasive procedure, it enabled us to get a tissue diagnosis which revealed that the opportunistic infection was actually caused by A. fumigatus . This was despite the negative result of the galactomannan antigen test; although this test has a relatively high sensitivity and specificity, it was falsely negative in this case [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Albeit this an invasive procedure, it enabled us to get a tissue diagnosis which revealed that the opportunistic infection was actually caused by A. fumigatus . This was despite the negative result of the galactomannan antigen test; although this test has a relatively high sensitivity and specificity, it was falsely negative in this case [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Galactomannan antigenemia is detectable via enzyme immunoassay up to a week before the onset of clinical manifestations of invasive aspergillosis, but is generally not observed in uninfected patients or those with Aspergillus colonization 69,70 . The utility of serum GM assays in asymptomatic immunocompromised populations has been an area of intensive investigation, and a recent Cochrane review 71 suggests that serial analysis may identify patients with IFI earlier than without screening. Some authorities suggest weekly or twice weekly screening of serum for GM during the first 100 days after allogeneic HSCT and during HM-related neutropenia.…”
Section: Diagnosis Of Hm/hsct Fungal Pneumioniamentioning
confidence: 99%
“…Una de las pruebas ampliamente utilizadas para este propósito es Platelia™ Aspergillus EIA (GM-EIA), un inmunoensayo enzimático que detecta la presencia de galactomanano (GM), principal componente de la pared celular de Aspergillus. El kit GM-EIA ha demostrado un buen rendimiento en el diagnóstico de AI a partir de muestras de suero 4,6 ; al utilizarse un índice de densidad óptica (IDO) de 0,5 como valor de corte. Se ha reportado una sensibilidad y especificidad aproximada de 78% y 81%; respectivamente 6 .…”
Section: Introductionunclassified
“…El kit GM-EIA ha demostrado un buen rendimiento en el diagnóstico de AI a partir de muestras de suero 4,6 ; al utilizarse un índice de densidad óptica (IDO) de 0,5 como valor de corte. Se ha reportado una sensibilidad y especificidad aproximada de 78% y 81%; respectivamente 6 . A pesar de que GM-EIA tiene un rendimiento diagnóstico aceptable, presenta …”
Section: Introductionunclassified